Hospital Management System Logistics 1: (Project Management, Asset Management, Warehousing, and Procurement): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research focuses on the functions of project management, warehousing, assetmanagement, and procurement in Hospital Logistics Part 1. The system needs to monitor andmanage the different parts of a logistics transaction in a hospital for the user to be moreproductive and have a reliable outcome and analysis. This system is for providing moreaccurate and reliable data about the transactions in the logistics part 1 of the hospital. Themain objective of this system is to provide efficiency in managing and monitoring the logisticsof the hospital's part 1 transaction.As a result, the researcher found out that the development of a reliable and efficient system formanaging logistics in hospitals is of great importance in ensuring the smooth flow of resourcesand supplies, which is essential for providing high-quality healthcare services. Theinvolvement of stakeholders and the use of daily standup meetings help to ensure that thesystem is designed and implemented to meet the needs of those who will use it.The researcher produces a system that can manage and monitor the transaction in logisticspart 1 of the hospital. This system helps the hospital to manage and monitor the transactionsin the logistics part 1 of the hospital. The system can improve the user's productivity and givethem efficiency in their work. The system can also ensure the security of the data andinformation input into it.
Keywords: IT & Management